Tantangan Perkawinan di Tengah Perubahan Sosial: Perspektif Keluarga Kontemporer - Angela Florida Mau (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This article explores the challenges facing marriage in the context of rapid social change, with a focus on contemporary family perspectives. Today, marriage is not only seen as a sacred bond, but also as an institution that must adapt to ever-changing social, economic, and cultural dynamics. Factors such as women's independence, shifting sex roles, and the influence of technology contribute to changes in partner selection patterns and family structures. Women's increased independence has caused many women to postpone marriage to pursue education and careers, which has implications for declining marriage rates. In addition, this article discusses how advanced couples seek to balance traditional values with the demands of today's life. Through this analysis, this article aims to provide insight into how contemporary families are facing these challenges and how they can build harmonious relationships in the midst of the changes that are occurring. By understanding these challenges, it is hoped that solutions can be found